Physical and Mechanical Properties of Jute Mat Reinforced Epoxy Composites - S.M Sadaf; M Siddik; Q Ahsan (Universitas Gadjah Mada, 2011)
Cellulose jute fibre offers a number of benefits as reinforcement for synthetic polymers since it has a high specific strength and stiffness, low hardness, relatively low density and biodegradability. To reduce moisture uptake and hence to improve the mechanical properties of the composites, bleached jute mats were incorporated as reinforcing elements in the epoxy matrix. Composites at varying volume fractions and different orientations of jute mat were fabricated by hot compression machine under specific pressures and temperatures. Tensile, flexure, impact and water absorption tests of composites were conducted. Jute mat oriented at (0 ± 45–90)° composites showed reduced strength compared to (0–90)° fibre mat composites. Impact strength and water uptake of high volume fraction jute mat reinforced composites was higher compared to that of lower volume fraction composites. Fracture surfaces of jute mat composites were analyzed under SEM. Fracture surface of (0–90)° jute mat oriented composites showed twisted fibres, while (0 ± 45–90)° jute mat oriented composites had fibre pull-out without any twisting. Overall, composites containing 52% jute mat at orientations of (0–90)° showed better properties compared to other fabricated composites.